Medications for Addiction Treatment: An Opportunity for Prescribing Clinicians to Facilitate Remission from Alcohol and Opioid Use Disorders - PARK, TAE WOO (R I Med J (2013), 2014)
Substance use disorders are a leading cause of morbidity and mortality in the United States. Medications for the treatment of substance use disorders are effective yet underutilized. This article reviews recent literature examining medications used for the treatment of alcohol and opioid use disorders. The neurobehavioral rationale for medication treatment and the most common ways medications work in the treatment of substance use disorders are discussed. Finally, the medications and the evidence behind their effectiveness are briefly reviewed. Physicians and other prescribing clinicians should take an active role in facilitating remission and recovery from substance use disorders by prescribing these effective medications with brief medical management counseling.